2006
DOI: 10.1038/nature04778
|View full text |Cite
|
Sign up to set email alerts
|

Detection of magnetic circular dichroism using a transmission electron microscope

Abstract: A material is said to exhibit dichroism if its photon absorption spectrum depends on the polarization of the incident radiation. In the case of X-ray magnetic circular dichroism (XMCD), the absorption cross-section of a ferromagnet or a paramagnet in a magnetic field changes when the helicity of a circularly polarized photon is reversed relative to the magnetization direction. Although similarities between X-ray absorption and electron energy-loss spectroscopy in a transmission electron microscope (TEM) have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
271
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(274 citation statements)
references
References 19 publications
1
271
0
2
Order By: Relevance
“…Plots of the OAM magnetic signal as function of the collection angle and sample thickness are shown for some example parameters, specified in the captions, in Figs. 4. In all cases one can see a magnetic signal reaching magnitudes of order 10 −5 varying strongly with both thickness and collection angle.…”
Section: Resultsmentioning
confidence: 83%
“…Plots of the OAM magnetic signal as function of the collection angle and sample thickness are shown for some example parameters, specified in the captions, in Figs. 4. In all cases one can see a magnetic signal reaching magnitudes of order 10 −5 varying strongly with both thickness and collection angle.…”
Section: Resultsmentioning
confidence: 83%
“…In order to invesitgate the changes in the ionisation edge fine-structure, we use WIEN2k to describe the target's states in the formula above. The MDFF needed in the first simulation package is calculated based on the cross-density of states (XDOS) and the wave functions of the target electron by TELNES.3 subroutines implemented in WIEN2k Schattschneider et al, 2006;Rusz et al, 2007).…”
Section: Simulationsmentioning
confidence: 99%
“…This distinction becomes important in, for example, inelastic scattering of atoms at non-zero impact parameters, since the reference frame is usually defined with the atom nucleus at the origin [1][2]. In electron energy loss magnetic circular dichroism (EMCD) measurements this would mean that an off-centred vortex beam would be in a mixed state with respect to the excited atom, rather than being a pure vortex beam of ±ħ angular momentum (note that besides vortex beams there are other methods for measuring EMCD, such as using the crystal as a beam splitter [3]). Indeed Schattschneider et al [4] have shown that in order to detect a strong dichroic signal the vortex probe should be localised at the excited atom.…”
Section: Introductionmentioning
confidence: 99%